Integration of Convergent Sensorimotor Inputs Within Spinal Reflex Circuits in Healthy Adults - Lopez, Alejandro J.; Xu, Jiang; Hoque, Maruf M.; McMullen, Carly; Kesar, Trisha M.; Borich, Michael R. (Frontiers in Human Neuroscience, 2020)
The output from motor neuron pools is influenced by the integration of synaptic inputs originating from descending corticomotor and spinal reflex pathways. In this study, using paired non-invasive brain and peripheral nerve stimulation, we investigated how descending corticomotor pathways influence the physiologic recruitment order of the soleus Hoffmann (H-) reflex. Eleven neurologically unimpaired adults (9 females; mean age 25 ± 3 years) completed an assessment of transcranial magnetic stimulation (TMS)-conditioning of the soleus H-reflex over a range of peripheral nerve stimulation (PNS) intensities. Unconditioned H-reflex recruitment curves were obtained by delivering PNS pulses to the posterior tibial nerve. Subsequently, TMS-conditioned H-reflex recruitment curves were obtained by pairing PNS with subthreshold TMS at short (-1.5 ms) and long (+10 ms) intervals. We evaluated unconditioned and TMS-conditioned H-reflex amplitudes along the ascending limb, peak, and descending limb of the H-reflex recruitment curve. Our results revealed that, for long-interval facilitation, TMS-conditioned H-reflex amplitudes were significantly larger than unconditioned H-reflex amplitudes along the ascending limb and peak of the H-reflex recruitment curve. Additionally, significantly lower PNS intensities were needed to elicit peak H-reflex amplitude (Hmax) for long-interval facilitation compared to unconditioned. These findings suggest that the influence of descending corticomotor pathways, particularly those mediating long-interval facilitation, contribute to changing the recruitment gain of the motor neuron pool, and can inform future methodological protocols for TMS-conditioning of H-reflexes. By characterizing and inducing short-term plasticity in circuitry mediating short- and long-interval TMS-conditioning of H-reflex amplitudes, future studies can investigate supraspinal and spinal circuit contributions to abnormal motor control, as well as develop novel therapeutic targets for neuromodulation.